FERMENTASI PAKAN DARI CAMPURAN LIMBAH KULIT KOPI SEBAGAI ALTERNATIF PAKAN TERNAK DI DESA KUTOREMBET KECAMATAN LEBAKBARANG: FERMENTASI PAKAN DARI CAMPURAN LIMBAH KULIT KOPI SEBAGAI ALTERNATIF PAKAN TERNAK DI DESA KUTOREMBET KECAMATAN LEBAKBARANG - Rihadatul Aisy, Adibah Husnaa (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2024)
The majority of the people of kutorembet village make a living as a livestock breeders and farmers. The problem in the livestock system in this village is that there are still many livestock breeders who only use wild grass as animal feed every day without knowing the nutrition of the feed. Therefore, the co0mmunity servuce team introduced one alternative feed to increase its storage capacity and nutritional content, namelyby utilizing coffee skin waste which is processed into fermented animal feed is one of the smart steps to overcome the shortage of food reserves for livestock during the dry season. The training was conducted at the Kutorembet Village Hall located in Dukuh Krajan. The stages of implementation in this study are observation, socialization and training. To implement this program, the community service team prepared equipment and voordinated with the Pekalongan Regency Food Security and Agriculuture Service. This training began wisth counseling with the food security and agricultureservice, then carried out joint practice of making fermented feed from coffee skin waste. The results of fermented coffee skin waste have good quality, seen from several mixed ingredients such as grass that dose not change color, the aroma is not rotten (typical of silage), the texture is not soft (dry), and is not moldy.